Pengendalian Kualitas Proses Produksi Rajungan Menggunakan Metode Seven Tools - Ni’matun Nafiah; Wahyudin Wahyudin; Dinda Habibah Azzahra (Jurnal Ilmiah Wahana Pendidikan, 2022)
The problem found was that there were defective crab products that made losses to the company and hampered the production process of making the crab itself. One method that can be used to solve the problems that have been described is the seven tools method. The seven tools method is to minimize the existence of defective crab products in order to achieve zero defects. This study aims to minimize losses that the company can get due to product defects. Reduction of defective products can affect the course of the crab production process. The cause of defective products is a machine that lacks maintenance, the method used is almost entirely manual labor and too much room movement, room temperature is not cold enough, raw material places are sometimes open, and lack of implementation of SOPs. The number of defective products is 910.09 kg with a span of 1 month. Crab meat which can be said to be defective has two elements, namely stale and soft elements, after analyzing the stale elements more than soft elements which if used in the presentation it is 70% and 30%. Some of the causes of product defects are machines, environment, methods, people, and materials